GREEN MARKETING PRACTICES: AN INVESTIGATION INTO CONSUMER PERCEPTIONS AND PURCHASE INTENTIONS - Verma, Jay Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Green marketing, an increasingly essential approach for businesses, promotes environmentally friendly products and sustainable activities. Using data gathered from 160 respondents via a structured questionnaire, this research explores consumer perceptions and consumer purchase intentions about green marketing strategies. The study’s goal is to discover critical elements impacting consumer behavior, such as environmental knowledge, belief in green promises, and perceived value of eco-friendly products. The findings reveal that consumer perceptions of green marketing have a significant impact on purchase intentions, underlining the need of firms communicating authenticity and aligning with consumer values. These results give practical insights for marketers to enhance their green marketing strategies and encourage sustainable consumption habits.